A Self-Evacuation Drill Development Program for Community Resilience against Mt. Merapi Disaster - Fathani, Teuku Faisal (2010)
Mt. Merapi is an active volcano in which the occurrence of the eruption is very frequent and produces significant disaster. As a part of disaster mitigation program, evacuation drills become very important not only for raising the community awareness, but also for increasing the community resilience against Mt. Merapi disaster. Various stakeholders from both related governmental agencies in Yogyakarta and Central Java Provinces, and private sectors, have introduced several drills at certain levels, mostly above the village levels. There are still few evacuation drill programs being conducted at the lower levels, in which community should conduct the first action when the disaster occurs. The presence of the facilities provided by the related government agencies would not be effective unless systematic evacuation system at sub-village levels is made available and frequently trained to the community. This paper presents the results of efforts in establishing the self-evacuation drills that are supposed to contribute beneficial in term of community resilience against Mt. Merapi disaster. The selection process of the model area is presented utilizing the community-based approach, so that the accommodated community aspiration may support the sustainability of the program. Three levels of alert that are now recognized by the local community are utilized to develop the program, including process of selecting the small group in charge in order to develop standard operating procedures, evacuation map, poster, and disaster preparedness organization. Method of self-evacuation drills implementation and its evacuation is presented and discussed accordingly, and recommendations for future replication of similar self-evacuation drills is promising beneficial for Mt. Merapi disaster mitigation program.